Age-dependent differences in the impact of paediatric traumatic brain injury on executive functions: A prospective study using susceptibility-weighted imaging. (18th February 2019) - Resch, Christine; Anderson, Vicki A.; Beauchamp, Miriam H.; Crossley, Louise; Hearps, Stephen J.C.; van Heugten, Caroline M.; Hurks, Petra P.M.; Ryan, Nicholas P.; Catroppa, Cathy
Abstract: Childhood and adolescence represent sensitive developmental periods for brain networks implicated in a range of complex skills, including executive functions (EF; inhibitory control, working memory, and cognitive flexibility). As a consequence, these skills may be particularly vulnerable to injuries sustained during these sensitive developmental periods. The present study investigated 1) whether age at injury differentially affects EF 6 months and 2 years after TBI in children aged 5–15 years, and 2) whether the association between brain lesions and EF depend on age at injury. Children with TBI ( n  = 105) were categorized into four age-at-injury groups based on previous studies and proposed timing of cerebral maturational spurts: early childhood (5–6 years, n  = 14), middle childhood (7–9 years, n  = 24), late childhood (10–12 years, n  = 52), and adolescence (13–15 years, n  = 15). EF were assessed with performance-based tasks and a parent-report of everyday EF. TBI patients' EF scores 6 months and 2 years post-injury were compared to those of typically developing (TD) controls ( n  = 42). Brain lesions were identified using susceptibility weighted imaging (SWI). Results indicated that inhibitory control performance 2 years post-injury was differentially affected by the impact of TBI depending on age at injury. Follow-up analyses did not reveal significant differences within the age groups, preventing drawing strong conclusions regarding the contribution of age at injury to EF outcome after TBI. Tentatively, large effect sizes suggest that vulnerability is most apparent in early childhood and adolescence. Everyday inhibitory control behaviour was worse for children with TBI than TD children across childhood and adolescence at the 2-year assessment. There was no evidence for impairment in working memory or cognitive flexibility after TBI at the group level. Given small group sizes, findings from analyses into correlations between EF and SWI lesions should be interpreted with caution. Extent, number and volume of brain lesions correlated with adolescent everyday EF behaviour 6 months post-injury. Taken together, the results emphasize the need for long-term follow-up after paediatric TBI during sensitive developmental periods given negative outcomes 2-year post injury. Inhibitory control seems to be particular vulnerable to the impact of TBI. Findings of associations between EF and SWI lesions need to be replicated with larger samples. Highlights: Inhibitory control has been established sensitive to (long-term) consequences of TBI. SWI is associated with parent-reported EF behaviour of adolescents. Early childhood and adolescence may be vulnerable periods for TBI impact on EF.